Antioxidant and Wound Healing Activity of Polyherbal Fractions of Clinacanthus nutans and Elephantopus scaber. (26th July 2016) - Aslam, Muhammad Shahzad; Ahmad, Muhammad Syarhabil; Mamat, Awang Soh; Ahmad, Muhammad Zamharir; Salam, Faridah
Abstract : Elephantopus scaber and Clinacanthus nutans are traditionally used as wound healing herb. The objective of the present study is to develop a new polyherbal formulation, by comparison, the herbal combination of Elephantopus scaber and Clinacanthus nutans as an in vitro antioxidant activity with their individual herbal activity followed by fractionation of polyherbal formulation for in vivo wound healing activities and identification of bioactive compounds from their active fractions. Antioxidant activity was performed in vitro by DPPH scavenging antioxidant activity followed by in vivo wound healing activities using excision wound model, incision wound model, and burn wound model. Toxicity of the fractions of the polyherbal formulation was performed by a dermal toxicity test. The result showed that Elephantopus scaber crude extract on the basis of EC50 performs a much faster action (15.67  μ g/mL) but with less % inhibition (87.66%) as compared to the combination of the new polyherbal formulation of crude extract (30  μ g/mL). The polyherbal formulation has the highest % inhibition (89.49%) at the same dose as compared to Elephantopus scaber (87.66%). In comparison among all crude and fractions of new polyherbal formulation, it was found that the ethyl acetate fraction of polyherbal formulation has the fastest activity (EC50 14.83  μ g/mL) with % inhibition (89.28%). Furthermore, during evaluation of wound contraction on excision and incision wound model, ethyl acetate fraction possesses the highest activity with ( P < 0.001) and ( P < 0.0001), respectively. During burn wound model, aqueous fraction ( P < 0.001) possesses the highest activity followed by an ethyl acetate fraction ( P < 0.0001). LC-MS analysis discovered the presence of several flavonoid-based compounds that work synergistically with sesquiterpene lactone and other bioactive compounds. In conclusion, flavonoid increases the antioxidant activity that surges the rate of wound contraction and works synergistically with other bioactive compounds.